Toolkit on the Appraisal of Small Renewable Energy Projects : Tanzania Case Study - World Bank (Washington, DC, 2014)
Following this introductory chapter, chapter two continues with a general description of the regulatory, institutional, and policy environment for Renewable Energy (RE) in Tanzania. The chapter describes the main existing institutional arrangements in place and shows that the country's legal framework is conducive to private sector RE initiatives. Chapter three discusses the fundamentals of project finance, the basic components of financial analysis, and common due diligence factors concerning RE investments. This discussion provides a framework for a better understanding of RE financing, which from a banker's point of view requires a different approach than the more traditional balance sheet-focused financing. Chapters 4 through 8 go over each of the most common RE technologies: chapter four: Hydropower; chapter five: biomass; chapter six: biogas; chapter seven: solar PV; and chapter eight: wind. Each of the chapters discusses both the basic technical and financial aspects of the technologies. Each chapter will provide the reader with a basic understanding of the technology in question and the associated financial challenges. In the chapters on hydropower (chapter four) and biomass (chapter five), a financial 'back-of-the-envelope' model is included as well.